Malawi : Poverty Reduction Strategy Paper; Growth and Development Strategy. (IMF Staff Country Reports; Country Report, 2007)
This paper focuses on the Poverty Reduction Strategy Paper (PRSP) and the Malawi Growth and Development Strategy (MGDS). The MGDS is the overarching strategy for Malawi from fiscal year 2006/07 to 2010/2011. The purpose of the MGDS is to serve as a single reference document for policymakers in government; the private sector; civil society organizations; donors and cooperating partners and the general public on socioeconomic growth and development priorities for Malawi. The overriding philosophy of the MGDS is poverty reduction through sustainable economic growth and infrastructure development.